Knowledge Management In the Development of State Civil Apparatus in the Honorary Council of Election Organizers of the Republic of Indonesia (DKPP RI) - Ridwan Wijayanto Said; Nurliah Nurdin; Tjahyo Suprayogo (INFOKUM, 2025)
The study aims to identify the causes of the suboptimal implementation of Knowledge Management in ASN development and formulate strategies to optimize its implementation. The research method used is a descriptive qualitative method with an inductive approach, using the SECI theory by Nonaka and Takeuchi and the SWOT analysis theory by Albert Humphrey. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that at the socialization stage, the lack of two-way communication, minimal incentives for sharing knowledge, and low interest in training are the main obstacles. At the externalization stage, weaknesses in document management and organizational discussions hinder the transformation of tacit knowledge into explicit knowledge. The combination stage is disrupted due to the ineffectiveness of the database system, which has an impact on decision making and career development. Meanwhile, at the internalization stage, limited Information Technology infrastructure, weak internet networks, and lack of mass media utilization slow down organizational learning. These findings emphasize the need to strengthen the system, knowledge sharing culture, and adequate technology and communication support to encourage effective knowledge management at the DKPP RI. Strategies that can be carried out by overcoming weaknesses include limited human resources, low budget, and lack of supporting facilities and infrastructure. Strategic opportunities lie in increasing human resource capacity, strengthening infrastructure, increasing budgets, and preparing internal regulations related to knowledge management. Meanwhile, the main challenges include disparities in employee education levels and the lack of ongoing evaluation and policies. By utilizing existing strengths and opportunities and anticipating weaknesses and threats, DKPP RI can build a more structured, sustainable knowledge management system that supports improving institutional performance.